Characterising Bdellovibrio bacteriovorus HD100 peptidoglycan modification genes during distinct cell cycle events - Somers, Hannah (2016)
Bdellovibrio bacteriovorus are predatory bacteria, which prey on other Gramnegative bacterial species. Bdellovibrio modiﬁes the cell wall peptidoglycan of its prey at several stages of its predatory life cycle: during invasion and entry into the prey periplasm, during the rounding of the prey into a stabilised bdelloplast (in which Bdellovibrio grow, replicate and divide) and at the end of the cycle, at which point the resulting progeny lyse the bdelloplast before repeating the predation process.